Hybrid Passive and Active Surveillance Approach with Interchangeable Filters and a Time Window Mechanism for Performance Monitoring - Prathap, M; Thanamani, Antony Selvadoss (International Journal of Computer Sciences and Engineering, 2025)
According to Bonald and Feuillet (2011), the management of network resources has taken on a new urgency with the highly interactive nature of modern computing and the increasing interdependence of networked applications. As a result, the monitoring of network behavior has become an integral part of management. It is critical that applications are armed with tools that can facilitate the estimation of performance and allow the selection of suitable encoding schemes, buffering sizes, and adaptation features. This paper examines the importance to assess the requirements for monitoring the network performance within a wireless environment for the processing and presentation of the statistical outcome of surveillance information. In comparison to the probing technique, which is based on the distance separating data packets, the two monitoring schemes lead to considerable traffic within the network. The proposed method will use a straightforward statistical analysis to determine variations in the network characteristics used a hybrid passive and active surveillance approach with interchangeable filters and a time window mechanism.